Application of Sociodrama Method to Improve Understanding of Nationalist Attitudes in Civic Education in Elementary Schools - Usma, Azhura (International Journal of Students Education, 2024)
This study aims to determine how to improve the understanding of nationalism attitudes in citizenship education in Elementary Schools by applying the sociodrama method. The research method used in this article is a systematic literature review, the author searched for articles that have been published. related to the title or topic of research that the researcher has determined. teachers or educators are able to find the right solution to foster a sense of nationalism in their students. improve the attitude of nationalism can be done in various ways, but not all students are the same in receiving learning, when learning takes place not all students are active and fully concentrated in the learning process. The ability to grasp each child is different, some are fast, medium or slow. From these differences the author concludes that this sociodrama is very interesting for students, allowing the class to be active and enthusiastic. This sociodrama method is also able to arouse enthusiasm in students so that students can foster a high sense of social solidarity.